2020
DOI: 10.21037/tau-20-1268
|View full text |Cite
|
Sign up to set email alerts
|

A urine-based biomarker for chronic prostatitis/chronic pelvic pain syndrome: a retrospective multi-center study

Abstract: Background: Chronic prostatitis (CP) or chronic pelvic pain syndrome (CPPS) is one of the most common diseases in young and middle-aged men, accounting for 30% of outpatient men in urology OPD. There are no definitive diagnostic criteria for CP or CPPS and no accepted therapies that cure the disease.Methods: We identified 372 patients with CP diagnosed from 2015 to 2018 and collect the information of age, routine urinary test, express prostatic secretion (EPS), and NIH-Chronic Prostatitis Symptom Index (NIH-CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Recently, several biomarkers in expressed prostatic secretion (EPS), urine, semen, or serum have been proposed for the diagnosis of CP/CPPS ( 7 , 38 40 ). Levels of urinary prostatic exosomal protein have been suggested as a novel biomarker for the diagnosis for CP/CPPS and can be used as a sign of the severity of CP/CPPS ( 41 ). Penna et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several biomarkers in expressed prostatic secretion (EPS), urine, semen, or serum have been proposed for the diagnosis of CP/CPPS ( 7 , 38 40 ). Levels of urinary prostatic exosomal protein have been suggested as a novel biomarker for the diagnosis for CP/CPPS and can be used as a sign of the severity of CP/CPPS ( 41 ). Penna et al.…”
Section: Discussionmentioning
confidence: 99%
“…quantified several cytokine and chemokine levels in seminal plasma of CP/CPPS patients and revealed that IL-8 in seminal plasma was significantly elevated in CP/CPPS patients and was positively correlated with symptom score. IL-8 is a reliable biomarker for CP/CPPS patients and can discriminate CP/CPPS IIIA versus IIIB ( 41 ). Watanabe et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic prostatitis (CP) is a common but confusing urological disease that seriously affects men's lives and health and cannot be ignored 1,2 . The incidence rate is increasing, and the disease is affecting younger men 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an urgent need to find biomarkers and detection methods that are non‐invasive, stable, simple, fast, accurate, and reliable. In recent years, the detection of prostatic exosomal protein (PSEP) in the urine has been reported in the clinical diagnosis of CP, 2,6 but since its diagnostic efficiency and application value are not completely clear, the study of urine PSEP and HSP70 in CP patients has not been reported. In this study, we measured and compared the levels of PSEP and HSP70 in the urine of patients with different types of CP and in control subjects and analyzed their role in the diagnosis and classification of chronic prostatitis.…”
Section: Introductionmentioning
confidence: 99%